Long-term stability of compression-molded soybean protein concentrate films stored under specific conditions - Ciannamea, Emiliano Manuel (2017)
Post-processing evolution of the functional properties of soybean protein concentrate (SPC) films, plasticized with varying levels of glycerol and processed by compression molding, was examined over a period of 90 days. Films stored in the glassy state (25 ± 2 °C and 65 ± 2% relative humidity) lost glycerol and water over time, as determined by gas chromatography and the decline in moisture content. SPC films plasticized with 40–50% glycerol showed a time-dependent increment of the elastic modulus and the tensile strength. In turn, the elongation, barrier properties, soluble mass and opacity of these films varied marginally with time. By contrast, films with 30% glycerol lost the most moisture and their elongation was reduced significantly, while water vapor permeability slightly increased with aging. The performance of aged films resulted from the balance between plasticizer and water loss, and the progressive replacement of unordered structures by intermolecular hydrogen bonded β-sheets and aggregates.